MENGUPAS PERSOALAN STANDAR AKUNTANSI KEUANGAN - GOODWIL DI BERBAGAI NEGARA : SUATU PENDEKATAN STUDI LITERATUR - Deddy Kurniawansyah (Universitas Airlangga, 2017)
This literature study explains and describe the development of the concept of goodwill from the perspective of accounting by observing and describing until the development at this time, discusses differences in accounting standards of goodwill applicable in some countries, and explains the things that contradict the goodwill. This research method used qualitative with literature study. The results of this study are in some countries, the concepts and rules on goodwill accounting have undergone various changes, including international accounting standards issued by the IASC. Initially goodwill is capitalized and amortized over no more than 20 years. But, along with the increasing use of fair value accounting in accounting standards, thetreatment for goodwill also experienced a shift that is eliminated by the amortization method is replaced by doing impairment test to goodwill. The results of this study contribute as add to the treasury of financial accounting literature, especially accounting treatment of goodwill as intangible assets in the financial statements of various countries such as Indonesia, America and the England.Keyword :Goodwiil, Impairment, Financial Accounting Standard